Studies of the Effects of Antibiotics on the Microflora of the Gastrointestinal Tract by Fluorimetry; Pharmaceutical Chemistry Journal; Vol. 50, iss. 4 - Bulycheva E. V. Elizaveta Vladimirovna (2016, 2016)
Title screen